Investigating car purchasing decision-making process using Multi- Objective Optimization Ratio Analysis based Analytical Hierarchy Process Model: An empirical case from Vietnam - NGUYEN, PHI-HUNG (The journal of contemporary issues in business and government, 2021)
This study aims to define and quantify the factors affecting selecting the best car among the market's available alternatives. Many criteria are involved while deciding to purchase the best car from various car models; therefore, car purchasing behaviour is a multi-criteria decision-making problem (MCDM). Proposed criteria are based on the customers’ survey when they are willing to purchase the cars, including Price, Branding, Safety, Performance, Exterior, Fuel efficiency, Maintainance cost, After-Sale Service, and Resale. In this study, the AHP technique calculates each criterion's weight, and then Multi-Objective Optimization Ratio Analysis (MOORA) is employed to rank the car models in a numerical example from Vietnam. The results show that this proposed model can minimize the consumer effort to select a car and make accurate decisions. Furthermore, this study's findings could provide car manufacturers with valuable insight into the criteria that reflect the customer's assessment of the car selection process. JEL: C02, C61, D53, Q14